Short-term and long-term prognoses in AChR-Ab positive very-late-onset myasthenia gravis patients - Nairong Xie; Qing Liu; Qi Wen; Yaye Wang; Haoran Liu; Yuting Jiang; Yan Lu; Li Di; Min Wang; Wenjia Zhu; Xinmei Wen; Xuxiang Zhang; et al. (Therapeutic Advances in Neurological Disorders)
Background: Very-late-onset myasthenia gravis (VLOMG) refers to myasthenia gravis (MG) with onset at age 65 or older. Current research on VLOMG prognosis remains limited, especially regarding factors influencing outcomes. Objectives: To identify the clinical factors that affect the short- and long-term prognosis of MG patients with an onset age ⩾65 years. Design: This was a single-center, retrospective cohort study of AChR-ab positive VLOMG patients, classified into two subgroups based on age of onset: sub-very-late-onset MG (S-VLOMG, onset age ⩾65 and <75 years), and super-late-onset MG (SLOMG, onset age ⩾75 years). Methods: A total of 93 patients were included, including 75 in the S-VLOMG group and 18 in the SLOMG group. Clinical, therapeutic, and prognosis data were reviewed, and the Cox regression model was used to identify factors influencing short- and long-term prognosis. Results: Patient characteristics were well balanced between the groups. Overall, 49.5% of patients achieved minimal symptom expression (MSE) within 6 months and 86% within 24 months. There was no significant difference between the groups in the proportion achieving MSE at 6 months ( p  = 0.635) or 24 months ( p  = 0.714). The median time to achieve MSE was also comparable between the S-VLOMG and SLOMG groups (199.0 days vs 280.5 days, p  = 0.463). Low baseline MG-ADL score and steroid therapy were associated with better short-term prognosis ( p  = 0.007 and p  = 0.002, respectively). For long-term prognosis, baseline bulbar and limb involvement, time to treatment initiation, and use of immunosuppressants were significant factors ( p  = 0.025, p  = 0.004, p  = 0.025, and p  < 0.0001, respectively). There were no significant differences in side effects or drug withdrawal rates between two groups. Conclusion: This study demonstrated that AChR-ab positive VLOMG patients have a favorable prognosis and responded well to medication, with age and comorbidities showing no significant impact.